Exploring the effect of vitamin D3 supplementation on the anti-EBV antibody response in relapsing-remitting multiple sclerosis. (September 2018) - Rolf, Linda; Muris, Anne-Hilde; Mathias, Amandine; Du Pasquier, Renaud; Koneczny, Inga; Disanto, Giulio; Kuhle, Jens; Ramagopalan, Sreeram; Damoiseaux, Jan; Smolders, Joost; Hupperts, Raymond
Background: Epstein–Barr virus (EBV) infection and vitamin D insufficiency are potentially interacting risk factors for multiple sclerosis (MS). Objectives: To investigate the effect of high-dose vitamin D3 supplements on antibody levels against the EBV nuclear antigen-1 (EBNA-1) in patients with relapsing-remitting multiple sclerosis (RRMS) and to explore any underlying mechanism affecting anti-EBNA-1 antibody levels. Methods: This study utilized blood samples from a randomized controlled trial in RRMS patients receiving either vitamin D3 (14, 000 IU/day; n  = 30) or placebo ( n  = 23) over 48 weeks. Circulating levels of 25-hydroxyvitamin-D, and anti-EBNA-1, anti-EBV viral capsid antigen (VCA), and anti-cytomegalovirus (CMV) antibodies were measured. EBV load in leukocytes, EBV-specific cytotoxic T-cell responses, and anti-EBNA-1 antibody production in vitro were also explored. Results: The median antibody levels against EBNA-1, but not VCA and CMV, significantly reduced in the vitamin D3 group (526 (368–1683) to 455 (380–1148) U/mL) compared to the placebo group (432 (351–1280) to 429 (297–1290) U/mL; p  = 0.023). EBV load and cytotoxic T-cell responses were unaffected. Anti-EBNA-1 antibody levels remained below detection limits in B-cell cultures. Conclusion: High-dose vitamin D3 supplementation selectively reduces anti-EBNA-1 antibody levels in RRMS patients. Our exploratory studies do not implicate a promoted immune response against EBV as the underlying mechanism.